The impact of study abroad social interactions on post-return relationships with international students: Japanese students’ perceptions of recategorization - Taniguchi, Norihito; Takai, Jiro; Iwaki, Nami (Frontiers in Education, 2025)
Previous research has focused on how students adapt to the host country during study abroad. However, less is known about how these experiences influence students’ social engagement upon returning home. This study explores how Japanese students’ social interactions abroad influence their relationships with international students in Japan after their return. Using a qualitative approach based on grounded theory, semi-structured interviews were conducted with 24 Japanese students who had studied abroad for one academic year. The findings suggest that social interactions abroad facilitate recategorization, a process in which individuals redefine group boundaries and develop a broader shared identity. This process was influenced by four key factors: language and social skills, motivation, opportunities, and perceived fit. Through this process, Japanese students expanded their group boundaries and formed a shared identity with international students in Japan as individuals with study abroad experience. As a result, they developed more positive attitudes toward international students, heightened empathy, and a stronger motivation to engage with and help international students. These findings indicate that recategorization can occur through the formation of a new social identity based on shared experiences rather than direct intergroup contact, highlighting the long-term impact of study abroad on students’ intercultural engagement. This study underscores Japanese students’ tendency to identify with international students in Japan rather than with host nationals upon their return.